Tissue-based quantitative proteome analysis of human hepatocellular carcinoma using tandem mass tags. (17th February 2017) - Megger, Dominik Andre; Rosowski, Kristin; Ahrens, Maike; Bracht, Thilo; Eisenacher, Martin; Schlaak, Jörg F.; Weber, Frank; Hoffmann, Andreas-Claudius; Meyer, Helmut E.; Baba, Hideo A.; Sitek, Barbara
Abstract: Context and objective: Human hepatocellular carcinoma (HCC) is a severe malignant disease, and accurate and reliable diagnostic markers are still needed. This study was aimed for the discovery of novel marker candidates by quantitative proteomics. Methods and results: Proteomic differences between HCC and nontumorous liver tissue were studied by mass spectrometry. Among several significantly upregulated proteins, translocator protein 18 (TSPO) and Ras-related protein Rab-1A (RAB1A) were selected for verification by immunohistochemistry in an independent cohort. For RAB1A, a high accuracy for the discrimination of HCC and nontumorous liver tissue was observed. Conclusion: RAB1A was verified to be a potent biomarker candidate for HCC.